2008
DOI: 10.1161/hypertensionaha.108.123042
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren Accumulates in Renin Secretory Granules and Binds Plasma Prorenin

Abstract: Abstract-The vascular effects of aliskiren last longer than expected based on its half life, and this renin inhibitor has been reported to cause a greater renin rise than other renin-angiotensin system blockers. To investigate whether aliskiren accumulation in secretory granules contributes to these phenomena, renin-synthesizing mast cells were incubated with aliskiren, washed, and exposed to forskolin in medium without aliskiren (0.1 to 1000 nmol/L). (Pro)renin concentrations were measured by renin-and proren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 29 publications
3
71
0
1
Order By: Relevance
“…[57][58][59] Also, aliskiren bound to the active form of prorenin in vivo. 60,61 On the other hand, this renin inhibitor did not blunt bindings of renin and prorenin to (P)RR, whereas it significantly decreased the mRNA expression of (P)RR in the kidney cortex of diabetic hypertensive Ren2 rats. 61 A peptide like renin inhibitor was first reported by Szelke et al 62 Peptides derived from the bovine pepsinogen (17 residues at the NH 2 -terminus of bovine and 1-16 residues of the porcine pepsinogens) were found to inhibit pepsin activity in a milk clotting assay at pH 5.5 with high values of K i .…”
Section: Effects Of Aliskiren Hrp/decoy and 'Hinge' Peptides On Renimentioning
confidence: 82%
“…[57][58][59] Also, aliskiren bound to the active form of prorenin in vivo. 60,61 On the other hand, this renin inhibitor did not blunt bindings of renin and prorenin to (P)RR, whereas it significantly decreased the mRNA expression of (P)RR in the kidney cortex of diabetic hypertensive Ren2 rats. 61 A peptide like renin inhibitor was first reported by Szelke et al 62 Peptides derived from the bovine pepsinogen (17 residues at the NH 2 -terminus of bovine and 1-16 residues of the porcine pepsinogens) were found to inhibit pepsin activity in a milk clotting assay at pH 5.5 with high values of K i .…”
Section: Effects Of Aliskiren Hrp/decoy and 'Hinge' Peptides On Renimentioning
confidence: 82%
“…The renin activity in this (pro)renin-aliskiren complex would be inhibited: this renin (or prorenin, which may undergo activation at tissue sites) could not cleave Aogen, and the tissue and systemic RAAS cascades would not be activated. As this mechanism should operate independently of plasma drug levels, 101 it may help to explain the prolonged BP benefits observed in rats discussed earlier, and in patients in whom aliskiren treatment has been stopped. 104 Aliskiren, prorenin and the (pro)renin receptor The recent discovery of a receptor for renin and prorenin, the (P)RR, 105 has added an important new dimension to the tissue RAAS.…”
Section: Aliskiren Localizes In the Kidneymentioning
confidence: 88%
“…However, a human mast cell line synthesizes and secretes (pro)renin. 100 Krop and coworkers 101 used these cells to ask whether aliskiren can incorporate into renin granules. They found that mast cells that had been incubated for 7 days with aliskiren secreted renin that displayed inhibited enzyme activity (that is, inhibited Ang I-forming capacity).…”
Section: Aliskiren Localizes In the Kidneymentioning
confidence: 99%
See 1 more Smart Citation
“…The detection limit of the EKA is 0.05 ng Ang I/ml per hour. Ang I-generating activities were converted to renin concentrations based on the fact that 1 ng Ang I/ml per hour corresponds with 2.6 pg human renin/ml (15). Before their application in the IRMA, the urine samples from the patients with hypertension and diabetes were concentrated 5-fold with Amicon Ultra-10 centrifugal filter devices (EMD Millipore, Cork, Ireland).…”
Section: Biochemical Measurementsmentioning
confidence: 99%